Microstructural and mechanical analysis of Cu and Au interconnect on various bond pads - Thangaraj, Joseph Sahaya Anand; Chua, Kok Yau; Yeow, See Leong; Lim, Weng Keat; Hng, May Ting (Elsevier, 2013)
Effects of High Temperature Storage (HTS) and bonding toward microstructure change of intermetallic compound (IMC) at the wire bonding interface of 3 types of bond pad (Al, AlSiCu and NiPdAu) were presented in this paper. Optical and electron microscope analyses revealed that the IMC growth rate of samples under 175 and 200 C HTS increased in the order of Al > AlSiCu > NiPdAu. Besides, higher HTS and bonding temperatures also promoted higher IMC thickness. The compositional study showed that higher HTS and bonding temperature developed rapid interdiffusion in bonding interface. In the mechanical ball shear test, a decrease of the shear force of Al and AlSiCu bond pads after 500 h HTS was believed due to poorly developed IMC at bonding interface. On the other hand, shear force degradation at 1000 h was due to excessive growth of IMC that in turn causes the formation of defects. For NiPdAu bond pad, increasing trend of shear force with HTS duration at 175 C implied a good reliability of the Cu wire bonding. The rapid microscopic inspection on Cu wired Al bond pad under HTS 175 C showed the IMC development from the periphery to the center of the ball bond. However, after 500 h voids started to develop until the crack was observed at 1000 h.